Early hypermetabolism is uncommon in trauma intensive care unit patients. Issue 4 (25th July 2020) - Byerly, Saskya; Vasileiou, Georgia; Qian, Sinong; Mantero, Alejandro; Lee, Eugenia E.; Parks, Jonathan; Mulder, Michelle; Pust, Daniel G.; Rattan, Rishi; Lineen, Edward; Byers, Patricia; Namias, Nicholas; et al.
Abstract: Background: Classic experiments demonstrating hypermetabolism after major trauma were performed in a different era of critical care. We aim to describe the modern posttraumatic metabolic response in the trauma intensive care unit (TICU). Methods: This prospective observational study enrolled TICU mechanically ventilated adults (aged ≥18) from 3/2018‐2/2019. Multiple, daily resting energy expenditure (REE) measurements were recorded. Basal energy expenditure (BEE) was calculated by the Harris‐Benedict equation. Hypometabolism was defined as average daily REE < 0.85*BEE and hypermetabolism defined as average daily REE > 1.15*BEE. Demographics, interventions, and clinical outcomes were abstracted. Descriptive statistics and multivariable logistical regression models evaluating demographics with the outcome variable of hypermetabolism for the first 3 days ("sustained hypermetabolism") were performed, along with group‐based trajectory modeling (GBTM). Results: Fifty‐five patients were analyzed: median age was 38 (28–56) years; 38 (69%) were male; body mass index (kg/m 2 ) was 28 (26–32); and Injury Severity Score was 27 (19–34), with (38 [71%] blunt, 8 [15%] penetrating, 7 [13%] burn) injury mechanism. Overall, 19 (35%) had hypermetabolism on day 1 ("immediate hypermetabolism"), and 11 (21%) had sustained hypermetabolism for the first 3 days. Logistic regression analysis identified penetrating mechanism (adjusted odds ratio [AOR], 16.4; 95% CI, 1.9–199.6; p = .015), burn mechanism (AOR, 11.1; 95% CI, 1.3–116.8; p =.029), and maximum temperature (AOR, 4.2; 95% CI, 1.3–20.3; p = .041) as independent predictors of sustained hypermetabolism. GBTM identified 4 nutrition phenotypes, with 2 hyperconsumptive phenotypes associated with increased risk of malnutrition at discharge. Conclusion: Only a minority of injured patients is hypermetabolic in the first week after injury. Elevated temperature, penetrating mechanism, and burn mechanism are independently associated with sustained hypermetabolism. Hyperconsumptive phenotype patients are more likely to develop malnutrition during hospitalization.